he Implementation of Character Education Management in Madrasah Aliyah - Aliyas Aliyas (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2019)
Abstract: The Implementation of Character Education Management in Madrasah Aliyah. The moral degradation that occurred among Indonesian generations has lead to endless unrest. The presence of several cases that do not reflect the dignified character of Indonesia often occurs. Therefore, the government moves to restructure the pattern of Indonesian education by presenting a character education program. Madrasah Aliyah is one of educational institutions that has an interest in character education programs by carrying out some good habituation activities carried out in madrasah. Implementation of character education management in Madrasas needed to involve all components of the madrasah, namely students, teachers and staff, madrasah principals, education leaders, and Santri parents. The use of this approach was based on a deep awareness that the success of an education was not only determined by the role of the school but also by the role of parents and society. The successful implementation of character education management was not only the responsibility of madrasah (madrasa principals and teachers), but also parents of students. Because the implementation of character education management was a shared responsibility between the madrasah headmasters, teachers and parents of students, each of them should be able to play a role as a supporter in the success of character education.Keywords: Implementation, Character Education Management